Assessment of Taungya agroforestry system in dryland forests rehabilitation in Sudan - Mohamed Hemida; Emad H E Yasin; Manal A Kheiry; Zeinab M Hammad; Andrea Vityi (Journal of Degraded and Mining Lands Management, 2023)
The decline of the forest cover due to deforestation and agricultural expansion in Sudan has reached a critical situation. Taungya agroforestry systems have been used as a strategy to safeguard against this process, allowing farmers to cultivate their subsistence crops at the early stage of tree plantations. The current study research tackled Nabag Forest Reserve (NFR) as a case study to assess and explore Taungya agroforestry system as a practice used for forest rehabilitation in the study area. Satellite images of Landsat 5 Thematic Mapper, and Landsat 8 Operational Land Imager/Thermal Infrared Sensor of 1991, 2001, 2011, and 2021 were used to generate forest cover maps. Both unsupervised and supervised classification, as well as ground truth points, were applied to classify the vegetation cover in NFR as dense forest (DF), light forest (LF), agricultural field (AF), and bare land (BL). The results showed that two trends of forest cover changes occurred in NFR between 1991-2001 and 2011-2021. It was well explored that through Taungya agroforestry, there was a considerable increase in forest cover over this period. This could be clearly detected by increasing dense forest and light forest cover by 1041.73 ha (24.95%) and 2.95 ha (0.07%), respectively and decreasing of bare land and agricultural field by 409.79 ha (9.81%) and 634.52 ha (15.15%) during the addressed period. The findings of the study indicated that Taungya agroforestry system could be a feasible land-use alternative for forest recovery in the dry land of Sudan.